MANAJEMEN, POLITIK DAN KEBIJAKAN PENDIDIKAN AGAMA ISLAM - Siti Rahayu NM (DAR EL-ILMI : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2019)
This paper presents a condition in which management, politics and policies in Islamic religious education. The trio is a unity that can not be separated from one another. Because they relate it takes good management, from planning, organizing, directing, monitoring and evaluation. In terms of education policy have a different phase when in the hands of a different leader, demonstrating the close relationship between political dominance in shaping policy in the implementation of the policy, especially education, especially Islamic education.